A new arylsulfanyl-benzo-2, 1, 3-thiadiazoles derivative produces an anti-amnesic effect in mice by modulating acetylcholinesterase activity. (5th January 2022) - da Costa Rodrigues, Karline; Leivas de Oliveira, Renata; da Silva Chaves, Julia; Esteves da Rocha, Vanessa Macedo; Fuzinato dos Santos, Beatriz; Fronza, Mariana Gallio; Luís de Campos Domingues, Nelson; Savegnago, Lucielli; Wilhelm, Ethel Antunes; Luchese, Cristiane
Abstract: The aim of the present study was investigate the binding affinity of 5-((4-methoxyphenyl)thio)benzo[c][1, 2, 5]thiadiazole (MTDZ) with acetylcholinesterase (AChE). We also evaluated the effect of MTDZ against scopolamine (SCO)-induced amnesia in mice and we looked at the toxicological potential of this compound in mice. The binding affinity of MTDZ with AChE was investigated by molecular docking analyses. For an experimental model, male Swiss mice were treated daily with MTDZ (10 mg/kg, intragastrically (i.g.)) or canola oil (10 ml/kg, i.g.), and induced, 30 min later, with injection of SCO (0.4 mg/kg, intraperitoneally (i.p.)) or saline (0.9%, 5 ml/kg, i.p.) daily. From day 1 to day 10, mice were submitted to the behavioral tasks (Barnes maze, open-field, object recognition and location, Y-maze and step-down inhibitory avoidance tasks), 30 min after induction with SCO. On the tenth day, the animals were euthanized and blood was collected for the analysis of biochemical markers (creatinine, aspartate (AST), and alanine (ALT) aminotransferase). MTDZ interacts with residues of the AChE active site. SCO caused amnesia in mice by changing behavioral tasks. MTDZ treatment attenuated the behavioral changes caused by SCO. In ex vivo assay, MTDZ also protected against the alteration of AChE activity, reactive species (RS) levels, thiobarbituric acid reative species (TBARS) levels, catalase (CAT) activity in tissues, as well as in transaminase activities of plasma caused by SCO in mice. In conclusion, MTDZ presented anti-amnesic action through modulation of the cholinergic system and provided protection from kidney and liver damage caused by SCO. Graphical abstract: Image 1 Highlights: Treatment with MTDZ protects cognitive damage caused by SCO in mice. MTDZ presents dual inhibition activity of AChE, both CAS and PAS. Treatment with MTDZ protects against AChE alteration on SCO model. MTDZ protects against damage on liver and kidney caused by SCO in mice.